The Energetics during the World's Most Challenging Mountain Ultra-Marathon—A Case Study at the Tor des Geants® - Savoldelli, Aldo; Fornasiero, Alessandro; Trabucchi, Pietro; Limonta, Eloisa; La Torre, Antonio; Degache, Francis; Pellegrini, Barbara; Millet, Grégoire P.; Vernillo, Gianluca; Schena, Federico (Frontiers in Physiology, 2017)
Purpose: To provide insights into the energy requirements as well as the physiological adaptations of an experienced 50-year-old ultra-marathon male athlete during the world's most challenging mountain ultra-marathon (MUM). Methods: The international race supporting the study was the Tor des Geants®, characterized by 330 km with +24,000 m D+ to be covered within 150 h. Before the MUM, we assessed the peak oxygen uptake (V˙O2peak) by means of an incremental graded running test. During the MUM we monitored six ascents (once per race day) with a portable gas analyzer, a GPS and a finger pulse oximeter. We then calculated the net metabolic cost per unit of distance (C), the vertical metabolic cost (Cvert) and the mechanical efficiency of locomotion (Effmech) throughout the six uphills monitored. We further monitored the distance covered, speed, altimetry and D+ from the GPS data as well as the pulse oxygen saturation with the finger pulse oximeter. Results: Subject's V˙O2peak was 48.1 mL·kg−1·min−1. Throughout the six uphills investigated the mean exercise intensity was 57.3 ± 6.0% V˙O2peak and 68.0 ± 8.7% HRpeak. C, Cvert and Effmech were 11.4 ± 1.9 J·kg−1·m−1, 57.9 ± 15.2 J·kg−1·mvert−1, and 17.7 ± 4.8%, respectively. The exercise intensity, as well as C, Cvert, and Effmech did not consistently increase during the MUM. Conclusions: For the first time, we described the feasibility of assessing the energy requirements as well as the physiological adaptations of a MUM in ecologically valid environment settings. The present case study shows that, despite the distance performed during the MUM, our participant did not experience a metabolic fatigue state. This is likely due to improvements in locomotor efficiency as the race progressed.